"Can We Say the N-word?": Exploring Psychological Safety During Race Talk. Issue 1 (2nd January 2016) - Williams, Jasmine D.; Woodson, Ashley N.; Wallace, Tanner LeBaron
Abstract : Classroom interactions that engender psychologically safe climates have rich developmental potential; these interactions often facilitate engagement in academic risk-taking and exploration (Cooper, 2013). On the contrary, classroom interactions that are threatening to adolescents' identities send messages of devaluation and can negatively impact feelings of belonging and academic achievement, particularly for youth of color (Sherman et al., 2013). In efforts to help explicate the interrelations between racial-identity linked risks and threats and psychological safety in classroom learning contexts, this exploratory case study examined two 9th grade English Language Arts teachers' negotiation of attunement, authenticity, and power sharing during race talk. Our in-depth analysis of these classrooms suggested the following teacher moves may be particularly important for psychological safety during race talk: teacher moves that (a) support or inhibit power sharing, (b) indicate high or low levels of teacher attunement, and (c) demonstrate or mask the teacher's authenticity. These results have implications for understanding the co-construction of psychological safety in classrooms during identity-salient and racialized interactions.